2009
DOI: 10.1021/pr800503u
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Archival Time on Shotgun Proteomics of Formalin-Fixed and Paraffin-Embedded Tissues

Abstract: There is increasing acceptance of the critical importance of correlating the morphologic features of tissue with the data obtained from various molecular analytic techniques. Access to archived formalin-fixed and paraffin-embedded (FFPE) tissue specimens via shotgun-based proteomic analyses may, therefore, open new avenues for both prospective and retrospective translational research. However, one of the remaining issues in performing comparative proteomic measurements among FFPE tissues relates to potential v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
81
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(88 citation statements)
references
References 37 publications
7
81
0
Order By: Relevance
“…We restricted the time period to 10 years in order to avoid loss of immunohistochemical reactivity [122]. Appropriate methods of statistical analysis were selected [30].…”
Section: Neuroendocrine Markersmentioning
confidence: 99%
“…We restricted the time period to 10 years in order to avoid loss of immunohistochemical reactivity [122]. Appropriate methods of statistical analysis were selected [30].…”
Section: Neuroendocrine Markersmentioning
confidence: 99%
“…Mass spectrometry data comparing extracts from fresh tissue and FFPE tissue for the same cell/ tissue sample (Table 2) support the notion that proteins extracted from FFPE tissue using heat-induced AR protocols are suitable for proteomics studies, as do data from protein array techniques (Prieto et al 2005;Rahimi et al 2006;Becker et al 2007;Becker et al 2009). For example, Balgley et al (2009) tested 10 archival FFPE tissue blocks with variable storage periods, as long as 28 years, by "shotgun" proteomics and found that high confidence and comparative proteome analysis were achieved in even the oldest tissue. In this context, AR-based methods, borrowed from the IHC field, are in like manner extending the usefulness and value of archival materials stored as paraffin blocks.…”
Section: Further Study To Improve Quality and Quantity Of Proteins Fomentioning
confidence: 99%
“…The few systematic studies addressing these factors have yielded contradictory results. For example, top-down proteomic studies report up to a 50% loss in recoverable protein from FFPE tissue blocks stored for 20 years [8], while bottom-up studies report little effect of storage time on protein identification by mass spectrometry (MS) [9]. One might question the value of considering preanalytical factors for FFPE proteomics because information on sample preparation is rarely available.…”
Section: The Role Of Preanalytical Factors In Ffpe Proteomic Analysismentioning
confidence: 99%